BRAC-char development and settlement project 2000 - 2004 - Banu, Dilruba (BRAC Research and Evaluation Division (RED), 2020)
Char Development and Settlement Project is designed to link the poor char people to mainstream development. Through five local NGOs the project commenced a series of interventions such as group formation and provision of credit, extension with regard to economic activities, and provision of health, legal and education services. BRAC has taken the role of monitoring and supporting institution of those local NGOs. This midterm evaluation aimed to review the progress of the project to date, and to determine the likelihood of achieving results at outcome level. The study shows a different economic strata in the char areas, 47% of the study population is identified as very poor which is quite high compared to the national average. The project covered 83% of the total eligible households of the sample areas who can join the VO. The activities of the project are likely gender sensitized. The expected outcomes, in the very small sample visited for this evaluation, appear to be generally positive in improving the socioeconomic condition of the project participants. The increased accesses to NGO credit, which the women's participation created for their husbands, have improved status of women at household level. At community level, the opposition voiced by the male section to women's participation in income earnings, was reported to be gradually declining over time, as women's contribution to household material well-being becomes evident. The likelihood of achieving expected outcomes for institutional environment of the VOs is generally considered to be quite high. Sustainability at individual level, in which VO members carry on the benefits of the project throughout their lives, is appropriate for the current phase of BRAC-CDSP.